Sight-threatening Diabetic Retinopathy and Associated Risk Factors Among Adult Diabetes Patients at Debre Tabor General Hospital, Northwest Ethiopia - Alemu Mersha G (Dove Medical Press, 2020)
Getasew Alemu Mersha,1 Asamere Tsegaw Woredekal,2 Matyas Tilahun Tesfaw3 1Department of Optometry, School of Medicine, University of Gondar Comprehensive Specialized Hospital, Gondar, Ethiopia; 2Department of Ophthalmology, School of Medicine, University of Gondar Comprehensive Specialized Hospital, Gondar, Ethiopia; 3Department of Ophthalmology, School of Medicine, Debre Tabor University, Debre Tabor, EthiopiaCorrespondence: Getasew Alemu MershaDepartment of Optometry, School of Medicine, University of Gondar Comprehensive Specialized Hospital, Gondar 196, EthiopiaTel +251932823935Fax +251-58-114 1240Email gechopta12@gmail.comBackground: People with diabetes have an increased risk of developing sight-threatening conditions. Sight threatening diabetic retinopathy (STDR) is an advanced microvascular of complication of diabetes on the eye. It remains one of the leading causes of preventable blindness among working age adults around the world. There is a paucity of evidence on the prevalence of STDR and its associated factors in Ethiopia, particularly in the study area. Therefore, the aim of our study was to determine the prevalence of STDR and its associated factors among adult diabetes patients at Debre Tabor General Hospital (DTGH), Northwest Ethiopia.Materials and Methods: An institution-based cross-sectional study was conducted on 306 diabetes patients at Debre Tabor General Hospital with systematic random sampling technique. Semi-structured questionnaire, document review and physical examination were applied to collect the data. Binary and multivariable logistic regression model were used to identify associated factors for STDR.Results: The majority of the participants 163 (53.3%) were type 1 diabetes (T1DM) and the mean age of T1 and T2 DM participants was 34.5 (12.8) and 58.7 (10.7) years respectively. The prevalence of STDR was 15.3% (95%CI: 9.6%– 20.9%) and 11.9% (6.6– 17.5) in T1DM and T2DM, respectively. Low family monthly income (adjusted odds ratio (AOR)=4.4, 95%CI: 1.05– 18.40) among T2DM, longer duration of diabetes (AOR=10.9, 95%CI: 2.94– 40.4) among T1DM (AOR=3.54, 95CI: 1.06– 11.8) among T2DM and poor glycemic control (AOR=3.93, 95%CI: 1.06– 14.5) and hypertension (AOR=5.86, 95%CI: 1.20– 28.6) among T1DM and BMI (AOR=4.79, 95%CI: 1.35– 17.00) among T2DM were significantly associated with STDR.Conclusion and Recommendation: The prevalence of STDR was high. Low family monthly income, longer duration of diabetes, poor glycemic control, hypertension and obesity were positively associated with STDR. Early screening of STDR and improving diabetes self management in all diabetes patients were recommended.Keywords: STDR, prevalence, Ethiopia